Interaction of the National Police of Ukraine and civil society institutions: concept and legal framework - V. V. Pylyp (Bulletin of Kharkiv National University of Internal Affairs)
In a state governed by the rule of law, the public plays a central role not only as a recipient of public services, but also as a subject involved in the implementation of many functions of state institutions. This involves not only public control over the activities of public authorities, but also the performance of tasks aimed at shaping the security environment in the state, performing law enforcement functions, etc.